2012
DOI: 10.1590/s1809-98232012000300010
|View full text |Cite
|
Sign up to set email alerts
|

Correlação entre estado nutricional e força de preensão palmar em idosos

Abstract: ResumoNo envelhecimento ocorrem mudanças corpóreas, dentre as quais a diminuição de massa magra com prejuízo na força muscular, afetando a capacidade funcional. Atualmente, o teste de Força de Preensão Palmar (FPP) está sendo utilizado para avaliar a força muscular global como auxiliar na avaliação nutricional. Objetivo: Verificar a correlação entre o estado nutricional e a FPP em idosos. Métodos: Estudo transversal realizado com idosos atendidos em ambulatórios de uma universidade pública federal. Para a clas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
15
0
28

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(52 citation statements)
references
References 16 publications
(18 reference statements)
3
15
0
28
Order By: Relevance
“…25 In terms of physical activity levels, no significant differences were found between the HGS means of the active and inactive groups and between the dominant and non-dominant side of each of these groups. This result corroborates the study by Souto et al 8 and Martin et al 26 which compared active and inactive individuals and did not find differences in strength between the dominant and non-dominant sides. However, in the study by Martin et al, 26 the practice of physical exercise was only self-reported and there was no separation of the type of exercise into aerobic and anaerobic, which may have influenced the findings of the study.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…25 In terms of physical activity levels, no significant differences were found between the HGS means of the active and inactive groups and between the dominant and non-dominant side of each of these groups. This result corroborates the study by Souto et al 8 and Martin et al 26 which compared active and inactive individuals and did not find differences in strength between the dominant and non-dominant sides. However, in the study by Martin et al, 26 the practice of physical exercise was only self-reported and there was no separation of the type of exercise into aerobic and anaerobic, which may have influenced the findings of the study.…”
Section: Discussionsupporting
confidence: 93%
“…This result corroborates the study by Souto et al 8 and Martin et al 26 which compared active and inactive individuals and did not find differences in strength between the dominant and non-dominant sides. However, in the study by Martin et al, 26 the practice of physical exercise was only self-reported and there was no separation of the type of exercise into aerobic and anaerobic, which may have influenced the findings of the study. The similar HGS results between the active and inactive groups of the present study may have been influenced by the fact that the inactive elderly persons were mostly low-income (up to two minimum wages) and were not institutionalized, suggesting greater active hand and wrist activity, correlated with HGS, during domestic chores.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Another important method to evaluate the changes of peripheral muscle strength, as this is one of the most important extra pulmonary manifestations of the COPD physiopathology (7), is the Hand Grip Strength (HGS). The HGS has as principle to estimate the musculoskeletal function through good reproducibility for the measurement of maximal manual voluntary handgrip strength, being considered a good index for overall muscle strength, and it can also reflect the impairment of the functional capacity (8).…”
Section: Discussionmentioning
confidence: 99%
“…Neste estudo, a maioria dos idosos não apresentou valores que indicassem tal perda, a qual já foi encontrada em outros estudos [21,23], inclusive no Inquérito Luso-Brasileiro de Nutrição Oncológica do Idoso [15]. Apesar do elevado percentual de eutrofia no IMC e na CP, observamos a desnutrição através da MANR, fato este que se justifica devido ao fato da MANR considerar o estado global de saúde.…”
Section: /7unclassified